2021
DOI: 10.3390/ijerph182312275
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Health: Methodological Approaches to Spatial Differentiation

Abstract: The prevalence of inequalities in the general health position of communities can be assessed by using selected determinants. The aims of this article are three-fold: (1) to apply a comprehensive approach to the assessment of inequalities in the general health position of communities, (2) to determine the spatial differentiation of determinants, and (3) to present selected assessment methods and their impact on the results. To present a quantitative assessment of these inequalities in health status in communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…The composite index method was used by Balode et al [14] to develop a methodology to pre-assess the impacts of policies identified in the NECP, a long-term energy and climate policy planning document that sets out the basic principles, measures and directions of Latvia's state energy and climate policy for the next ten years. In the study of Hübelová et al [15], a composite indicator (health index) was developed to present a quantitative assessment of inequalities in health conditions between districts in the Czech Republic. This index is composed of eight areas of evaluation: economic conditions and social protection, education, demographic indicators, environmental conditions, individual living conditions, road safety and crime, health and social care resources, and health status; a total of 60 indicators have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The composite index method was used by Balode et al [14] to develop a methodology to pre-assess the impacts of policies identified in the NECP, a long-term energy and climate policy planning document that sets out the basic principles, measures and directions of Latvia's state energy and climate policy for the next ten years. In the study of Hübelová et al [15], a composite indicator (health index) was developed to present a quantitative assessment of inequalities in health conditions between districts in the Czech Republic. This index is composed of eight areas of evaluation: economic conditions and social protection, education, demographic indicators, environmental conditions, individual living conditions, road safety and crime, health and social care resources, and health status; a total of 60 indicators have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the WSA method, a weighted sum method based on utility maximization principles, to calculate these composite indicators. This method assumes linearity and maximization of all partial utility functions, obtained by normalizing the original input data (see [25] for more details on the methods). We used Pearson's correlation coe cient for a correlation analysis to identify relationships between the categories of health inequalities.…”
Section: Methodsmentioning
confidence: 99%
“…In the second phase the same method was used for the complete categories A.1 to A.7 together and with equal weights. This result could be taken as the aggregate index of determinants of health inequalities of each district (see [ 24 ] for more details on the methods). In the WSA method criteria can be minimized or maximized.…”
Section: Methodsmentioning
confidence: 99%
“…The framework is modular and scalable. We also applied different methodological approaches to spatiotemporal analysis and comparison of results [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation